The energy expenditure in boarsailors - Jaszczur-Nowicki, J.; Smulskij, V. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Traditionally the VO2 is one of the fundamental indexes of aerobic processes in the energy expenditure in the athletes who have been examined in the laboratory with the use of treadmill or a cycloergometer. But laboratory conditions (physical loads) do not correspond to the real boardsailing, especially while pumping. Thus, the main purpose of our examinations was to compare the energy expenditure in laboratory and the simulation exercises of boardsailing which are similar to those ones at low and high winds. Methods The examinations were carried out at the Academy of Physical Education and Sport in Gdansk. Eleven boardsailors were subject to the examinations. A portable the COSMED metabolimeter, for evaluation of the VO2 and VCO2 values was used. The device allowed us to calculate RQ and the energy expenditure (kJ kg-1·min-1 (kkal kg-1·min-1) as well as the sum of kJ during 40 min. exercise (that corresponds to a single race) at average HR of 142 and 168 bpm, which stands up to regatta conditions at high (6 - 7 B0) and low (1 - 2 B0) winds respectively [1]. The statistic analysis included determination of Means (SD) and statistic reliable difference between indexes by Za - criterion of symbols [2]. Results The results of our examinations (see table) have given evidence between the energy cost of the boardsailors while working on the cycloergometer and those at the simulation exercises of boardsailing. It concerns, in particular to the VO2 ml·kg-1·min-1, kJ kg-1·min-1 and the sum of kJ after 40 min exercise indexes at HRav : 168 bpm (but not HRav : 142 bpm). In spite of the reliable differences in these indexes at t-Student criterion, but by Za - criterion of symbols these differences were statistic reliable (a < 0, 01). Discussion/Conclusions The results of our examinations have proved significant energy expenditure in the boardsailors at low wind. It may be related to submaximum aerobic power where the oxygen enrgy is at the level of 95% [3]. Considering the boardsailors take part in 4 races a day, so the energy expenditure may by dependent on the boardsailors` performance. Moreover, our results have proved significant energy expenditure in the elite boardsailors at HRav : 168 bpm during windsurfing simulator test (more 2500 kJ). But during cycloergometer test. this index is always higher. Our findings should be carefully interpreted when refer to the cycloergometer testes.